Eye dominance and minor physical anomalies in schizophrenia: relations between two biological markers of abnormal neurodevelopment - Akabalieva, Katerina (Frontiers in Psychiatry, 2023)
Background To investigate the frequency of left eye dominance and minor physical anomalies (MPAs) in schizophrenia patients and control subjects and determine the interrelations of these two biological markers of neuronal dysontogenesis in schizophrenia. Subjects and methods Three tests for eye dominance were administered as performance tasks, not preference questionnaires. Seven MPAs were examined. The sample consisted of 180 (98 schizophrenia patients and 82 control subjects). Several statistical methods for examining the eye tests separately and together were used to assess the difference in left-eyedness between schizophrenia patients and control subjects. Results Left eye dominance is significantly higher in schizophrenia subjects. Left-eyed subjects are more stigmatized with MPAs. There is a strong positive correlation between left-eyedness and stigmatization with MPAs in schizophrenia patients. Conclusion As hand dominance is under cultural pressure, eye dominance is culturally independent and is useful and reliable indicator of altered hemispheric lateralization. The significant positive correlations between left-eyedness and MPAs and the high concurrence of these biological markers in schizophrenia patients are a potent indicator of underlying aberrant neurodevelopment.